Systemic Expression, Purification, and Initial Structural Characterization of Bacteriophage T4 Proteins Without Known Structure Homologs - Zhang, Kaining; Li, Xiaojiao; Wang, Zhihao; Li, Guanglin; Ma, Biyun; Chen, Huan; Li, Na; Yang, Huaiyu; Wang, Yawen; Liu, Bing (Frontiers in Microbiology, 2021)
Bacteriophage T4 of Escherichia coli is one of the most studied phages, whose research has led to numerous contributions to phage biology and biochemistry. Coding about 300 gene products, this double-stranded DNA virus is the best-understood model in phage study and modern genomics and proteomics. Ranging from viral RNA polymerase commonly found in phages to thymidylate synthase whose mRNA requires eukaryotic-like self-splicing, its gene products provide a pool of fine examples for phage research. However, there are still up to 130 gene products that remain poorly characterized, despite being one of the most-studied model phages. With the recent advancement of cryo-electron microscopy, we have a glimpse of the virion and the structural proteins that present in the final assembly. Unfortunately, proteins participating in other stages of phage development are absent. Here, we report our systemic analysis on 22 of these structurally uncharacterized proteins, of which none has known homologous structure due to the low sequence homology to published structures and does not belong to the category of viral structural protein. Using NMR spectroscopy and cryo-EM, we provided a set of preliminary structural information for some of these proteins including NMR backbone assignment for Cef. Our findings pave the way for structural determination for the phage proteins, whose sequences are mainly conserved among phages. While this work provides the foundation for structural determinations of these proteins like , Gp57B, Cef, Y04L and Mrh, other in vitro studies would also benefit from the high yield expression of these proteins.